Extended Abstracts of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411763.3443454
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Virtual Reality Myoelectric Prosthesis Training System for Amputees

Abstract: Electrical signals produced by muscle contractions are found to be effective in controlling accurately artificial limbs. Myoelectric-powered can be more functional and advantageous compared to passive or body-powered prostheses, however extensive training is required to take full advantage of the myoelectric prosthesis' usability. In recent years, computer technology has brought new opportunities for improving patients' training, resulting in more usable and functional solutions.Virtual Reality (VR) is a repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Future testing will evaluate how training reduces time and improves accuracy in grasping. In previous studies, participants have performed similar myoelectric training [25], but in those cases the user only had to interact with the environment according to a single mode. In this study, the users can try different ways to interact with the assistive robot, so that they have the opportunity to choose the one that best suits their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Future testing will evaluate how training reduces time and improves accuracy in grasping. In previous studies, participants have performed similar myoelectric training [25], but in those cases the user only had to interact with the environment according to a single mode. In this study, the users can try different ways to interact with the assistive robot, so that they have the opportunity to choose the one that best suits their needs.…”
Section: Discussionmentioning
confidence: 99%
“…The virtual hand is usually represented by a game element or visualisation. Interacting with objects in the XR environment typically involves attaching them to the hand through programming, rather than controlling the virtual hand using a myoelectric controller that mimics the functionality of the prosthetic hand ( Hargrove et al, 2018 ; Nissler et al, 2019 ; Phelan et al, 2021 ) compared the virtual TAC test with a set of outcome measures for physical prostheses, including SHAP, JTHF, BBT, and CRT. Their findings showed a correlation between virtual test measurement and physical performance, but no causal relationship was found.…”
Section: Existing Challenges and Future Developmentmentioning
confidence: 99%
“…Noninvasive myoelectric sensing has been explored in human-device interaction studies, including teleoperation [20], user understanding [43], VR/AR training [55], and upper-limb [18] and lower-limb prostheses [21], and rehabilitation [33, 47, 50, 56]. From an HCI perspective, these studies demonstrated an accessible alternative to traditional manual devices like mice and keyboards for users with upper-limb motor impairments [70].…”
Section: Related Workmentioning
confidence: 99%